Brand Image Produk KITA: Upaya Meningkatkan Volume Penjualan di Perum Bulog - Muh. Hamzah; Fathor Rozi; Farida Nurul Aisyah (Ekonomis: Journal of Economics and Business, 2023)
This research aims to know about KITA Product Image Brand Implementasi an effort to add the sales promotion in Bulog communal housing. This research is done in Bulog communal haousing of Bondowoso with qualitative reconcilititation at outdooor study. Data submitted thecnic trough interview, yard note, and other documents to get data and information that’s gonna be explained by three informan keys viz: Asistent Manager of Ritel, Asistent Manager of Minku, and Staff of Commerse part. Analysis procces data of researcher troug data reduction, data presentation, and concluding finding result. Till this shows the succes of image boand implementation to add the sales promotion in Bulog communal housing. To develop sales promotion through 4 indicators: conclucting marketing promotion, service treating to consumen, the variasit price is achieved, and the variasit of nutrions product. The type implementation can develop the sales promotion in Bulog communal nousing in Bondowoso branch.